(3JMaI GdWdGH TQM JfbjM GddHGHs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s ((3MGQH Hf eMeO Hf PjGH Hf MGQH s)
(3ChdgG (B:s
(3GdMeO ddg GdPi abg ai Ojfg ef EUWaGg ef GdCfGe hHYO agPG TQM Ydi eNJUQi GdeSei HJMQjQ JfbjM GddHGH ai Gdabg Ydi ePgH GdEeGe GdeLJgO GdTGaYi QVi Gddg Yfg s
(3BNQgG (B:s
(3hdh cGf CMO CHhjg eQJOkG h GdBNQ cGaQkG CUdjkG acGaQ CUdi , bGdg GdHZhi hGddg CYde Je gPG GdcJGH GdeSei TQM GdJMQjQ HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3HChdgG agQSJ ddeNWhW s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3Gdabg GdESdGejs